[tex]y = \frac{1}{2} (4x - 6) - 3(0.25x - 2) \\ y = 0 \\ \frac{1}{2} (4x - 6) - 3(0.25x - 2) = 4 \\ 2x - 3 - 0.75x + 6 = 4\\ 1.25x + 3 = 4 \\ 1.25x = 4 - 3 \\ 1.25x = 1 \\ x = 1 \div \frac{5}{4} \\ x = \frac{4}{5} \\ x = 0.8[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]y = \frac{1}{2} (4x - 6) - 3(0.25x - 2) \\ y = 0 \\ \frac{1}{2} (4x - 6) - 3(0.25x - 2) = 4 \\ 2x - 3 - 0.75x + 6 = 4\\ 1.25x + 3 = 4 \\ 1.25x = 4 - 3 \\ 1.25x = 1 \\ x = 1 \div \frac{5}{4} \\ x = \frac{4}{5} \\ x = 0.8[/tex]